A spill over effect of entrepreneurial orientation on technological innovativeness: An outlook of universities and research based spin offs - Scuotto, Veronica (Springer Nature, 2020)
By shifting towards Romer’s (Am Econ Rev 94:1002–1037, 1986) economy and so the spread of knowledge economy, universities started to adopt a collaborative approach with their entrepreneurial ecosystem. They turn out to be risk taker, autonomous, proactive, competitive, and innovative. In a nutshell, they are entrepreneurial oriented with the aim to generate new innovative ventures, known as research-based spin ois. Doubly, this has induced an improvement of technology transfer and the degree of entrepreneurship in the current knowledge economy. However there still is a paucity of studies on the spill over eiect of entrepreneurial orientated universities and research-based spin oi on technology transfer need to be more explored. Therefore, the article investigates the link between entrepreneurial orientation and such spill overs by oiering an outlook of two universities and two research-based spin ois in the United Kingdom. The scope is to provide a deep view of technological innovativeness in a research context, entrepreneurial oriented. Our research suggests that entrepreneurial attitude has become an imperative to succeed in the context where British institutions currently operate. Entrepreneurship brings the necessary technological innovation to the university and its students, which results in better positioning of the university at national and international levels, with the subsequent impact on their ability to attract not only new students and academics but also funding to conduct their research.